2021
DOI: 10.1037/per0000433
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bonding impairment predicts personality disorder features in adolescence: The moderating role of child temperament and sex.

Abstract: Research has shown associations between adverse parenting experiences and (borderline) personality disorder ([B]PD). A biopsychosocial model suggests that child characteristics and the environment interact in the development of symptoms. However, prospective data in this aspect are limited. This study focused on maternal bonding impairment (MBI; 2 weeks postpartum) and its interactions with child temperament (age 5) and child sex as predictors of BPD symptoms and general personality dysfunction in adolescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Importantly, "adverse (childhood) experiences, biological predisposition, or a combination of both may disrupt these virtuous cycles," which in turn may lead to low resilience and vulnerability for psychopathology (Luyten et al, 2020). Research investigating this pathway to psychopathology is accumulating (Back et al, 2021), and since recently, there is first longitudinal evidence for the interaction of temperamental features in early childhood and parental caring skills as a predictor of PF 14 years later (Fleck et al, 2021). Viewed from this angle, differences in PF impairment in individuals reporting ACE found in our study may be an indicator for predispositional vulnerability that only comes into effect in the interaction with unfavorable environmental influences such as ACE.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, "adverse (childhood) experiences, biological predisposition, or a combination of both may disrupt these virtuous cycles," which in turn may lead to low resilience and vulnerability for psychopathology (Luyten et al, 2020). Research investigating this pathway to psychopathology is accumulating (Back et al, 2021), and since recently, there is first longitudinal evidence for the interaction of temperamental features in early childhood and parental caring skills as a predictor of PF 14 years later (Fleck et al, 2021). Viewed from this angle, differences in PF impairment in individuals reporting ACE found in our study may be an indicator for predispositional vulnerability that only comes into effect in the interaction with unfavorable environmental influences such as ACE.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Studies have shown that establishing an early emotional link can lead to more positive parenting behaviors and that such a link can protect against social and emotional maladjustment in the child; in contrast, failure to establish such a bond during infancy can have serious longterm effects on the parent-infant relationship, which may lead to child neglect or abuse and affect the child's psychosocial development. 1,4 Various factors can compromise the formation of a close and positive parent-infant relationship. 5,6 For example, studies have shown that parents with depression had a difficult time adjusting to parenthood and were less sensitive to their infants' cues, which may result in less than optimal bonding with their infants.…”
Section: Introductionmentioning
confidence: 99%
“…Parent‐infant bonding refers to a close emotional tie that the parent develops with the infant 2,3 . Studies have shown that establishing an early emotional link can lead to more positive parenting behaviors and that such a link can protect against social and emotional maladjustment in the child; in contrast, failure to establish such a bond during infancy can have serious long‐term effects on the parent‐infant relationship, which may lead to child neglect or abuse and affect the child's psychosocial development 1,4 …”
Section: Introductionmentioning
confidence: 99%
“…We examined a community sample of 76 adolescent-mother dyads who participated in a longitudinal study on temperament and the development of BPD traits [ 47 49 ]. Adolescents (46% girls) were 14.0 (SD = 0) years old, mothers on average 48.2 years old (SD = 4.6).…”
Section: Methodsmentioning
confidence: 99%